Análise do potencial de modelos contrastivos em tarefas de imagem-para-grafo - Takeda, Eduardo Minoru (Universidade Federal de São Carlos, 2025)
Large Vision-Language Models (VLMs) have demonstrated capabilities in various image-related tasks, such as object detection, recognition, and counting. However, they still face significant challenges when dealing with images of graphs and diagrams. Given this landscape, it becomes crucial to investigate both methods to adapt these models and methodological alternatives capable of exploiting their true capabilities. Among possible approaches, Contrastive Learning stands out for achieving results superior to other models involving multiple textual attributes and positional dependencies. In this context, investigating the capabilities of the CLIP model proves pertinent, especially considering the advancement of other multimodal models across different domains. This work analyzes the potential of CLIP, coupled with Contrastive Learning, for tasks involving the extraction of similarity between graph images and the recognition of their edge lists, as well as the differentiation of graph structures. Results were positive regarding edge list recognition, while the clustering of different structures and degrees of regularity showed promising potential, albeit still requiring further exploration and fine-tuning. The analysis of metrics and the expansion of the methodology's applications may contribute significantly to advancing the state of the art in the field.
On the potential of contrastive models in image-to-graph tasks
Keywords: Modelos de visão e linguagem; Grafos; Aprendizado contrastivo; Similaridade de grafos; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO; 3. Saúde e Bem-Estar; 9. Indústria, Inovação e Infraestrutura